Salvifarinin A, a neo-clerodane diterpenoid with a 6/5/7 tricyclic skeleton from Salvia farinacea. Issue 32 (8th August 2018) - Fan, Min; Chen, Xue-Jiao; Wu, Xing-De; Shao, Li-Dong; Ji, Xu; Zhao, Qin-Shi
Graphical abstract: Highlights: Isolation of a novel diterpenoid with unprecedented skeleton from Salvia farinacea. The absolute configurations of 1 and 3 were confirmed by single crystal X-ray data. Compound 2 displayed a potent effect on reducing hepatic steatosis. Abstract: Salvifarinin A (1 ), a rearrangement product of Languidulane-type clerodane diterpenoids with a 6/5/7 tricyclic ring skeleton fused with γ -lactone ring and furan ring, and two new biogenetically related diterpernoids, salvifarinins B (2 ) and C (3 ), were isolated from the aerial parts of Salvia farinacea . The absolute configuration of 1 was elucidated by extensive spectroscopic methods, and confirmed by single crystal X-ray diffraction and bio-inspired semisynthesis. The plausible biogenetic pathway was also proposed. Compound 2 displayed a potent effect on reducing hepatic steatosis.